Reform of Indirect Taxes in India through the Plexus of Goods and Services Tax (GST); A post-COVID 19 Fiscal Stimulus - Khan, Ruby; Khan, Shabnam (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
GST is a major tax reform in India that has been in the works for a long time due to political concerns and competing stakeholders' interests. It was first launched in April 2010, but the goods and services tax (GST) went into effect on July 1, 2017. The primary goal of GST is to consolidate all indirect taxes in India, including the central excise tax (CET), the value-added tax (VAT), and the service tax, into a single taxation structure. It improves the country's taxation system by increasing transparency and reducing tax evasion and corruption. The GST concept, its features, GST advantages, and their influence on the Indian economy are all discussed in this article.